5 - L’État et la société en Afrique - ANYANG'NYONG'O, P. (Africa Development, 1983)
Marxist literature on theories of the state has been in resurgence since the early seventies. With regard to Africa, a great deal of attention has been focused on «the post-colonial state» ever since the publication Hamza ALAVI's essay in the New Left Review (July/August 1972) «The State in Post-Colonial Societies: Pakistan and Bangladesh». ALAVI focused on the character of ruling classes in post-colonial societies, their historical evolution, their relationship to the metropolitan bourgeoisie and their interactions with the state. The weak and underdeveloped bourgeoisie finds itself unable to use the overdeveloped colonial state apparatus in its own interests or in the national interest. Instead, it must content itself with governing under the hegemony of the metropolitan bourgeoisie. This is a structural and historical limitation to the actions of the bourgeoisie in post-colonial societies; it says nothing about incredulity, lack of vision, corruptness, etc.. which FANON heaped on it. While ALAVI's hypotheses have been useful in analysing post colonial states in various African situations, we find it more perceptive conceptualize the state in post-colonial societies as a variant of the talist state. The modern state in Africa, it is argued in this paper, is a talist state of a neo-colonial variety. It has institutions, apparatuses, processes and ideology that defend and reproduce the capitalist social order under its neo-colonial conditions. As a capitalist state, it is a phenomenon that has its effects within a specific territory called the nation-state. theory, the state is independent of the interests of any particular individual and appears to represent the interest of the nation as a whole. In practice, it protects the interests of the economically dominant classes who are ble of using state power to change the legal order and, hence, redefine what the state should defend as a law. The manner in which a particular ruling class forms its own domi nation and rules politically defines the kind of regime that exists in a parti cular post-colonial society. Thus, while the very structure of the neo-Jl/al state will put limits to the actions of the ruling classes as laid out ALAVI, the specificity of every historical situation and the class struggles going on in such situations will define the kinds of regimes that may emerge from time to time. The general weakness of the bourgeoisies in colonial societies makes its difficult for them, however, to develop hegemo nic ideologies for their rule in such societies. The general tendency, there fore, is the development of disjunctures between the supposedly legitima ting ideologies and the concrete socio-economic realities in Africa s post colonies. The end result is a general gap between the ruling class and the masses, a gap generally filled by dictatorships of various sorts or regimes of pacts of domination. This essay is essentially exploratory. The author is conscious of the fact that several ideas here are still «primitive»; they may need to developed as a result of feedbacks from readers. That kind of interaction and exchange of ideas is, in the final analysis, the aim of Africa Development. P. ANYANG'NYONG'O, Coordinateur El Colegio De Mexico, AC